Worlds as Transcendental and Political Fictions - Benčin, Rok (Filozofski vestnik, 2024)
By examining the idea found in the works of several contemporary philosophers that the multiplicity of worlds is no longer merely possible – as it was for Leibniz – but actually determines our experience of reality, the article proposes an understanding of worlds as transcendental structures that frame the ontological multiplicity. The article argues that such a proliferation of actual worlds implies that the concept of world should be seen today as a category that belongs to the order of fiction, making the world-building devices of literature relevant for understanding the contemporary experience of reality. The first part examines the conceptions of multiple worlds of Leibniz, Deleuze, and Badiou through the structural differences and similarities between possible and fictional worlds. While Deleuze actualises possible worlds, Badiou actualises fictional worlds. The second part explores worlds as political fictions, revisiting Kant’s conception of cosmopolitanism via Rancière’s definition of politics as a conflict of worlds. Rancière’s formulation of political dissensus in fictional and narrative terms sheds a new light on Kant’s description of cosmopolitanism as a perspective that presents history as a novelistic narrative.